Optimal choice of acetylcholinesterase reactivators for antidotal treatment of nerve agent intoxication - Bajgar, Jirí (Acta medica (Hradec Kralove), 2010)
The studies dealing with mechanism of organophosphates (OP)/nerve agent action, prophylaxis and treatment of intoxications is a very hot topic at present. Though the research is very intensive, unfortunately, up to now, there is not universal or significantly better reactivator sufficiently effective against all nerve agents/OP when compared with presently available oximes (pralidoxime, methoxime, obidoxime, trimedoxime, HI-6). The use of the most effective reactivator (HI-6) using simple type of autoinjector (e.g. ComboPen) is strictly limited because of decomposition of HI-6 in solution. Thanks to better solubility it is clear that another salt of HI-6 (dimethanesulfonate, HI-6 DMS) is more convenient for the use as antidote against nerve agents in the autoinjector than HI-6 chloride (Cl). It was clearly demonstrated that reactivation potency of HI-6 DMS in comparison with HI-6 Cl in vivo was the same and bioavailability of HI-6 DMS is better than that of HI-6 Cl. Three chambered autoinjector allows administration of all three antidotes (atropine, reactivator, diazepam) simultaneously. Moreover, the content of chambers can be changed according to proposed requirements. Possible way to solve the problem of universal reactivator could be the use of two reactivators. Three chambered autoinjector is an ideal device for this purpose.
Keywords: pyridinové sloučeniny; cholinesterasové inhibitory; Cholinesterase Reactivators; Oximes; oximy; otrava organofosfáty; Animals; Chemical Warfare Agents; Humans; lidé; Pyridinium Compounds; zvířata; antidota; Cholinesterase Inhibitors; Organophosphate Poisoning; Antidotes; reaktivátory cholinesterasy; chemické bojové látky